Organic Alternatives to Quantum Dots for Intraoperative Near-Infrared Fluorescent Sentinel Lymph Node Mapping - Shunsuke Ohnishi; Stephen J. Lomnes; Rita G. Laurence; Andrew Gogbashian; Giuliano Mariani; John V. Frangioni (Molecular Imaging, 2005)
Intraoperative near-infrared (NIR) fluorescence imaging provides the surgeon with real-time image guidance during cancer and other surgeries. We have previously reported the use of NIR fluorescent quantum dots (QDs) for sentinel lymph node (SLN) mapping. However, because of concerns over potential toxicity, organic alternatives to QDs will be required for initial clinical studies. We describe a family of 800 nm organic heptamethine indocyanine-based contrast agents for SLN mapping spanning a spectrum from 775 Da small molecules to 7 MDa nanocolloids. We provide a detailed characterization of the optical and physical properties of these contrast agents and discuss the advantages and disadvantages of each. We present robust methods for the covalent conjugation, purification, and characterization of proteins with tetra-sulfonated heptamethine indocyanines, including mass spectroscopic site mapping of highly substituted molecules. One contrast agent, NIR fluorescent human serum albumin (HSA800), emerged as the molecule with the best overall performance with respect to entry to lymphatics, flow to the SLN, retention in the SLN, fluorescence yield and reproducibility. This preclinical study, performed on large animals approaching the size of humans, should serve as a foundation for future clinical studies.